STRATEGI DAN PENGARUH KUALITAS PRODUK,HARGA DAN LOKASI TERHADAP KEPUASAN KONSUMEN KULINER SEBLAK DI BATURAJA KABUPATEN OGAN KOMERING ULU - Putri, Shelly Rizkita; Ogari, Putri Ayu; Pusvita, Ema (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Seblak is a typical and contemporary food originating from Bandung, West Java, made from crackers cooked with vegetables along with eggs and other spicy flavors. In its development seblak became food that can be enjoyed by many people. This study aims to determine: 1) To determine the effect of product quality, price, and location on Seblak consumer satisfaction in Baturaja, Ogan Komering Ulu Regency. 2) To formulate a strategy to increase consumer satisfaction with Seblak in Baturaja, Ogan Kota Regency. This research method was carried out using quantitative methods and descriptive qualitative methods quantitative methods using multiple linear regression analysis. Qualitative descriptive method using data collection techniques through questionnaires and observations related to improving strategies in identifying strengths, weaknesses, opportunities and threats with the SWOT method on seblak in Baturaja, Ogan Komering Ulu Regency. Through IFAS (Internal Factor Analysis Strategy) and EFAS (External Factor Analysis Strategy) factors. From the results of proving the first hypothesis, product quality has a significant effect on satisfaction. From the results of the second hypothesis that price partially has a significant influence on satisfaction. From the results of proving the three hypotheses, locations partially have a significant influence on satisfaction. From the results of the fourth hypothesis, product quality, price and location simultaneously have a significant influence on satisfaction. From this study it can be seen that the calculation of the EFAS matrix is 2.0 and the IFAS matrix is 2.13 which is then depicted in the SWOT diagram, so it can be seen that the position of increasing growth in cell II indicates that the strategy is experiencing growth through horizontal integration. Horizontal integration is a process of increasing production, where this strategy, if one makes a decision, can be a good strength and a good opportunity.